Preliminary test of the potential of contact with dogs to elicit spontaneous imitation in children and adults with severe autism spectrum disorder - Silva, K.; Lima, M.; Fafiães, C.; Sinval, J.; De Sousa, L. (American Journal of Occupational Therapy, 2020)
Importance: Finding strategies to enhance imitation skills in people with autism spectrum disorder (ASD) is of major clinical relevance. Objective: To evaluate whether contact with dogs may be a useful approach to elicit spontaneous imitation in people with ASD. Design: Participants completed a spontaneous imitation task under three experimental conditions: after a free-play interaction with a live dog, after a free-play interaction with a robotic dog, and after a waiting period that involved no stimuli. Participants: Ten children and 15 adults diagnosed with severe ASD. Outcomes and measures: Imitation ratio, imitation accuracy, and indicators of social motivation. Results: Children appeared more motivated and engaged more frequently in spontaneous imitation in the live dog condition than in the other conditions. No differences between conditions were found for adults for imitation or social motivation. However, correlations suggested a possible trend for adults in time spent engaging with the live dog before testing and in increased imitation frequency. Conclusions and relevance: The results are preliminary and do not indicate the utility of integrating (live) dogs into interventions aimed at promoting social motivation and enhancing imitation skills in people with ASD. However, they suggest that doing so holds promise. Larger scale studies are now needed. What this article adds: This research calls for occupational therapy practitioners' attention to the potential benefits that may derive from using dogs to promote spontaneous imitation, and increase imitation performance, in people with ASD, particularly children.